2020
DOI: 10.2298/vsp180626132s
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between metabolic syndrome quantification scores and numerous laboratory parameters related to this syndrome

Abstract: Background/Aim. Metabolic syndrome (MS) is characterized by basic cluster risk factors-waist circumference (WC), glucoregulation disorders, hypertension, hypertriglyceridemia, low HDL-cholesterol followed by associated factors such as insulin resistance (IR), C-reactive protein (CRP), uric acid, plasminogen activator inhibitor-1 (PAI-1), fibrinogen, hyperhomocysteinemia (HHcy), nonalcoholic fatty liver disease (NAFLD) and microalbuminuira. The aim of this study was to analyze basic and associated factors of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The use of the siMS score can be useful both in diagnosis and as a useful tool for assessing the overall improvement or worsening of the disease in the prognostic monitoring of the patient, and some researchers point out that it can also be used as a biomarker for MS. Statistically significant correlation of siMS score with NAFLD parameters (ALT, GGT, FLI), uric acid, CRP, log CRP, in both groups and with PAI-1, microalbuminuria and homocysteine ​​in the elderly group proves that all these parameters are associated factors of MS. In agreement with the current results, our earlier research in obese patients with MS and without MS showed a positive correlation of the siMS score with CRP, uric acid, microalbuminuria, homocysteine, ​​and fibrinogen as associated factors of MS ( Sreckovic et al, 2020 ). In another study we found that patients with MS had higher values of co-founding factors of MS (HOMA-IR, CRP, uric acid, ALT, GGT), this is confirmed by correlation with siMS score.…”
Section: Discussionsupporting
confidence: 93%
“…The use of the siMS score can be useful both in diagnosis and as a useful tool for assessing the overall improvement or worsening of the disease in the prognostic monitoring of the patient, and some researchers point out that it can also be used as a biomarker for MS. Statistically significant correlation of siMS score with NAFLD parameters (ALT, GGT, FLI), uric acid, CRP, log CRP, in both groups and with PAI-1, microalbuminuria and homocysteine ​​in the elderly group proves that all these parameters are associated factors of MS. In agreement with the current results, our earlier research in obese patients with MS and without MS showed a positive correlation of the siMS score with CRP, uric acid, microalbuminuria, homocysteine, ​​and fibrinogen as associated factors of MS ( Sreckovic et al, 2020 ). In another study we found that patients with MS had higher values of co-founding factors of MS (HOMA-IR, CRP, uric acid, ALT, GGT), this is confirmed by correlation with siMS score.…”
Section: Discussionsupporting
confidence: 93%
“…Of the included papers, 26 directly associated UA with MetS 28 30 , 33 , 35 , 36 , 38 , 40 – 46 , 48 50 , 56 , 57 , 59 61 , 63 , 65 , 66 , 72 , and 17 reports collected data indirectly 27 , 31 , 32 , 34 , 37 , 39 , 47 , 51 53 , 57 , 58 , 64 , 68 70 , 74 , i.e. they study parameters related to MetS and collect data associated with UA.…”
Section: Discussionmentioning
confidence: 99%
“…Of the included papers, 26 directly associated UA with MetS [28][29][30]33,35,36,38,[40][41][42][43][44][45][46][48][49][50]56,57,[59][60][61]63,65,66,72 , and 17 reports collected data indirectly 27,31,32,34,37,39,47,[51][52][53]57,58,64,[68][69][70]74 , i.e. they study parameters related to MetS and collect data associated with UA.…”
Section: Discussionmentioning
confidence: 99%